Pemodelan Kondisi Geologi Teknik Daerah Amblesan Tanah Jalan Semarang Outer Ring Road (SORR) - Masvika, Hendra; Cahyono, Dhamang Budi; Wanto, Sri (Jurnal Pengembangan Rekayasa dan Teknologi, 2021)
The Semarang Outer Ring Road (SORR) project which is located on soft soil has the potential to experience land subsidence due to consolidation. The consolidation settlement is predicted to continue along with the length of time the consolidation is completed. It is necessary to study subsurface engineering geology to obtain an overview of the structure of the soil layers and the thickness of the soft soil layer that has the potential to undergo consolidation. Based on the data of 4 borehole points and the results of laboratory tests, evaluation and correlation were carried out to obtain the stratigraphy of the soil layer. The stratigraphic results showed that the total depth of the soil investigation was 50 m, with the surface soil layers generally consisting of embankment soil, sandy clay, sandy silt, and clayey silt. The distribution of clay and silt with very soft to medium consistency dominates the soil layer structure with a thickness varying between 15.50-28.00 m. This condition has the potential to cause an increase in the magnitude and rate of consolidation due to the surface loading of the embankment soil.